Broadband high-sensitivity acoustic sensing based on Brillouin random fiber laser. (June 2023) - Pang, Yuxi; Ma, Shaonian; Zhao, Xian; Qin, Zengguang; Liu, Zhaojun; Xu, Yanping
Highlights: A fiber-optic acoustic sensor based on Brillouin random fiber laser is proposed and experimentally demonstrated. The acoustic sensing is realized by utilizing the sensitivity of the lasing output of BRFL filtered by the DCFRR to external acoustic disturbances that mediate the cavity length of the DCFRR. Broadband acoustic frequency response ranging from 2 Hz to 200 kHz is achieved with high sensitivity. Abstract: In this study, a broadband high-sensitivity fiber-optic acoustic sensor with simple structure and low cost based on Brillouin random fiber laser (BRFL) is proposed and demonstrated theoretically and experimentally. A double coupler fiber ring resonator (DCFRR) in the BRFL, which filters out redundant random modes and ensures high-quality lasing output, is utilized as the sensing element for acoustic sensing thanks to the high sensitivity of the transmission spectrum of the DCFRR to its cavity length variations induced by acoustic perturbations. The resultant shift in the transmission spectrum of the DCFRR by the external acoustic vibrations modulates the gain available inside the BRFL cavity and transfers the resonant random mode, leading to directly modulated lasing intensity output from the BRFL and thus the feasibility for acoustic signal recovery. The experimental results demonstrate the broadband frequency response and high sensitivity feature of the proposed BRFL-based acoustic sensor, which is able to detect acoustic signals in both low-frequency (2 Hz ∼ 500 Hz) and high-frequency (0.5 kHz ∼ 200 kHz) regions with high signal-to-noise ratio beyond 10 dB. In addition, the structural flexibility of the proposed sensor enables remote acoustic sensing, making it an ideal candidate for acoustic applications in harsh environments.